Characterization of wheat root traits for adaptability to abiotic stress - Nevescanin Moreno, Antonia Lucia Guadalupe (2024)
Agricultural production seems to have a hostile future, current agrosystems are facing a tough reality coping with complex challenges like a growing population and climate change; this means breeders must not just meet the production demand, but also improve the capacity of the crops to fit in new adverse climate conditions. Wheat is not the exception of these problems and it has a big area of opportunity related to crop improvement. Plant phenotyping is a powerful tool that helps to identify the traits which shall be necessary as inputs to design well adapted crops, but it´s well known that most of the attention is on the aboveground part of the plant. Despite playing a crucial role in acquiring resources, roots are often neglected mainly because of the challenges associated with measuring belowground structures. Thus, the aim of this PhD project is to identify wheat root traits for improved adaptation to diverse environmental stressors, by characterizing root traits for drought and heat adaptation and utilizing hormone related sensitivity as an innovative approach to predict and enhance root growth under soil compaction conditions.